PENGARUH PEMANASAN BERULANG (TYNDALISASI) SAUS SPAGHETTI IKAN TUNA TERHADAP DAYA TERIMA DAN PENDUGAAN UMUR SIMPAN DENGAN METODE AKSELERASI MODEL PERSAMAAN ARRHENIUS: (Influence of The Recurrent Heating (Tyndalization) Spaghetti Sauce of Tuna on The Acceptance and Estimation of Shelf Life with Acceleration Method of Arrhenius Equation Model) - Maryati Bilang; Andi Dirpan; Nur Sakinah (jurnal1, 2018)
Spaghetti sauce of tuna is a processed product of tomato (Lycopersicum esculentum) with the addition of tuna and added some seasoning. It has a typical taste and as a complement to eat spaghetti. This research was divided into two stages, the preliminary research stage aimed to find out the best treatment of tuna spaghetti sauce which was treated with recurrent heating 1 to 3 times of heating wherein interval 24 hours for each time of heating, with the criteria was organoleptic test results (color, flavor, and flavour) and total microbes. From the preliminary research results obtained the best spaghetti sauce treatment has A2 treatment with 2 times heating. The main research in this study aimed to determine the shelf life of the best sample by using the Arrhenius model acceleration method. The product has stored in 3 different temperatures at 31oC, 38oC and 45oC. Analyzes and parameters used were pH measurement, total microbes, total titrated acids, color and organoleptic brightness levels that include aroma and taste. The result of microbial analysis was TPC as the key parameter, the shelf life of tuna spaghetti sauce was 78 days or 2.6 months while from physical analysis (organoleptic) that has the flavor as the key parameter, the age of tuna spaghetti sauce was 267 days or 8.9 months.